Solve the system using substitution
![Solve the system using substitution class=](https://us-static.z-dn.net/files/de6/119ed43da0d1366cb51e88fb478cffa7.png)
Answer: Option B
No solutions
Step-by-step explanation:
We have the following system of equations
[tex]2x - y = -6[/tex] (1)
[tex]-4x + 2y = -9[/tex] (2)
To solve the system using the substitution method, solve the first equation for the variable y
[tex]y=2x+6[/tex]
Now substitute the value of y in the second equation
[tex]-4x + 2(2x +6) = -9[/tex]
[tex]-4x + 4x +12=-9[/tex]
[tex]12=-9[/tex]
2 is not equal to -9, the system is inconsistent. The system has no solution
Answer:
No solution
Step-by-step explanation:
Given equations are 2x-y=-6 and -4x+2y=-9.
Now we need to solve that system of equation using substitution method.
solve 2x-y=-6 for y
2x-y=-6
-y=-6-2x
y=6+2x
Plug this value of y into other equation -4x+2y=-9
-4x+2(6+2x)=-9
-4x+12+4x=-9
12=-9
Which is a false equation.
Hence there is no solution to the given system.